Exploring Critical Success Factors in Agritourism: A Mixed-Methods Approach - Pafun Nilsawas Duhamel; Shubham Pathak; Josephine Ling Chen Yii; Pasakorn Thammachote (Journal of Human, Earth, and Future)
Agritourism is an alternative approach to distributing economic and social advantages and fostering sustainable development in rural regions. This research aims to identify critical success factors of agritourism to comprehend the obstacles and problems associated with Thailand and examine the essential factors of achieving success. The research adopts a mixed-method approach to collect, analyze, and interpret qualitative and quantitative aspects. The data was collected by reviewing documents, conducting in-depth interviews, conducting questionnaires, making onsite observations, and conducting focus group discussions. The questionnaires were sent to a panel of experts from educational institutions, the Ministry of Agriculture and Cooperatives, the Ministry of Tourism and Sports, and the tour operators. The data analysis involved paired t-tests and factor analysis to provide a comprehensive analytical output. The findings revealed four critical success factors in the Thai agritourism industry: geographical location, the entrepreneurial mindset of the farm operators, the quality of products and stories, and social media and publicity strategies. Agritourism sites in famous areas were found to have more potential for success, and an entrepreneurial mindset allows farmers to create attractions and diversify products. Therefore, knowing how to use new communication channels helps farmers deal with customers and better understand customer needs.